Fifty years of quasars : from early observations and ideas to future research - Marziani, Paola; Sulentic, Jack W.; D'Onofrio, Mauro (Astrophysics and Space Science Library, 2012)
The 50th anniversary of the discovery of quasars in 1963 presents an interesting opportunity to ask questions about the current state of quasar research. Formatted as a series of interviews with noted researchers in the field, each of them asked to address a specific set of questions covering topics selected by the editors, this book deals with the historical development of quasar research and discusses how advances in instrumentation and computational capabilities have benefitted quasar astronomy and have changed our basic understanding of quasars. In the last part of the book the interviews address the current topic of the role of quasars in galaxy evolution. They summarise open issues in understanding active galactic nuclei and quasars and present an outlook regarding what future observational facilities both on the ground and in space might reveal. Its interview format, the fascinating topic of quasars and black holes, and the lively recollections and at times controversial views of the contributors make this book both rewarding and a pleasure to read!